The use of mobile solutions for biomechanical assessment in combat sports: A narrative review - Sant`Ana, J.; Kons, R. L.; Detanico, D.; Diefenthaeler, F. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
New technologies have amplified the possibilities for processing and incorporating data and scientific methods in algorithms through the integration of the use of mobile technology and a wide range of wearables that allow acquisition metrics in real-time. These technologies arise as a possible alternative to supply market demand and to present practical solutions to problems that coaches and athletes face in their daily routines. Concerning biomechanical assessment in combat sports (i.e. reaction time, velocity, and force), the literature is scarce regarding studies that carried out surveys of new assessments and monitoring technologies, with solutions for coaches and athletes. Therefore, the current study aimed to investigate, through a literature review, mobile technologies available on the market for biomechanical analyses in combat sports modalities. Significant growth has been observed in the number of studies involving mobile technologies with practical tools for biomechanical assessment in combat sports athletes. However, only seven technological proposals presented scientific reliability studies, and six assessed validity, showing the necessity of more original articles to investigate scientific validation. As a suggestion, a flowchart is presented with operational guidelines for the research and development of new technologies for biomechanical assessment and monitoring in combat sports in real-time.